Reply to the Comment on "Exploiting Electronic Strategies to Stabilize a Planar Tetracoordinate Carbon in Cyclic Aromatic Hydrocarbons" by V. S. Thimmakondu,: Chem. Commun., 2019 Doi: 10.1039/C9cc04639a - Pino-Rios, R (Royal Society of Chemistry, 2019)
The effectiveness of our proposed approach to stabilize a planar tetracoordinate carbon (ptC) in cyclic aromatic hydrocarbons, introduced in the title article, is unquestionable as our exhaustive searches on the singlet and triplet potential energy surfaces of the new ptC molecules identified as viable species are reproducible. Besides, the T1 diagnostic value for the Si2C5H2 system reported in the comment seems to be the T1 amplitudes. We recomputed the T1 diagnostic value using different software (Gaussian and ORCA), which gave similar values to that reported in our communication. Additionally, a multiconfigurational (complete active space SCF) calculation fully confirms the mono-configurational character of the questioned Si2C5H2 ptC structure. We accept that the linear isomer for the C7H2 system, in the triplet electronic state, is competitive with the isomer reported in our article, in the singlet electronic state, as mentioned in the title comment. However, this is a minor correction that does not affect the primary goal and main conclusions of our communication. This journal is © The Royal Society of Chemistry.